COMPREHENSION READING SKILLS THROUGH CIRC METHOD IN GRADE IV STUDENTS OF SD INPRES 3 TONDO - Sitti Harisah; Ira Hikmawati (Universitas Tadulako, 2020)
The main problem in this research is the low ability to read understanding students of IVA SD Inpres 3 Tondo class. The study uses the CIRC method. The purpose of this research is to improve the learning skills of students ' understanding through the class CIRC method of IVA SD Inpres 3 Tondo, involving 24 students, consisting of 10 males and 14 women enrolled in the school year 2019/2020.This type of research is classroom action research. This type of research is classroom action research. The research uses the & Mc Taggart model consisting of 4 stages: planning, implementation, observation, and reflection. The study carried out 2 cycles. Data is collected through observation and final test of action. The results showed that the classical absorbent power of reading students' understanding at the preview was 62.91%, and the classical learning lead was 50%.In cycle I increased with the acquisition of classifying force reading students' understanding of 76.67% and classical learning submission to 66.67%. In cycle II increased with the acquisition of classical absorption by 83.55% with the acquisition of classical learning for the 87.5%. Based on the percentage of student learning outcomes of cycle I and cycle II, there has been a significant increase, i.e., in the classical absorbent power increased by 83.55%. Thus, it can be concluded that learning by implementing the CIRC method can improve comprehension reading skills in the students of IVA SD Inpres 3 Tondo class. Hypothetical action in this study is acceptable.